Archaizmy w idiolekcie poetyckim Nadieżdy Teffi (Heteroglossia – studia kulturoznawczo-filologiczne, 2022)
This subject of the research is the problem of linguistic image of the world in Nadezhda Teffi’s poetry. The analysis was focused on the idiolect of the poetess – a Russian émigré from the “first wave”. This article is devoted to lexical and grammatical archaisms appearing in her works that appeared in three poetry collections: Семь огней (1910), Passiflora (1923), Шамрам. Песни Востока (1923). The volumes, containing both early works from the pre-revolutionary evolution of poetess’s language and the entire process of the evolution of her poetic idiolect.